(untitled) (Biological Sciences - PJSIR, 2002)
Chloroacetyl pyrimidine was synthesized and reacted with both aromatic amines and hydrazine hydrate. Hydrazide was reacted with !3-dicarbonyl compounds and also with different acid anhydrides. 2-Amino-pyrimidine afforded new Schiff ’s bases which were cyclized with thioglycolic acid and thiolactic acid . Thiosemicarbazido derivatives were cyclized to give thiadiazole which gave Mannich bases. Some of the newly prepared compounds were biologically tested as antimicrobials